2012
DOI: 10.17129/botsci.474
|View full text |Cite
|
Sign up to set email alerts
|

Dinámica de Phragmites australis y Schoenoplectus americanus en respuesta a la adición de fósforo y nitrógeno en humedales experimentales

Abstract: 3Autora para la correspondencia: yazminelb@yahoo.com.mxResumen: Las especies invasoras, como Phragmites australis, resultan grandes competidoras para las especies nativas; sin embargo, es poco lo que se conoce sobre el mecanismo de invasión. En este trabajo se evaluó la interacción de P. australis con una especie nativa, Schoenoplectus americanus, mediante un experimento de parcelas divididas con adición de nutrimento (nitrógeno y fósforo). Para P. australis se encontraron diferencias (P < 0.05) entre tratamie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Other studies have suggested that environmental factors likely to influence reed bed expansion include seasonal fluctuations in water levels and nutrient influxes from the lake bottom and surrounding river systems (Liira et al ; Catford et al ). However, based on the response of other wetland plants and other Schoenoplectus species to seasonal water fluctuations and nutrient increases (Escutia‐Lara & Lindig‐Cisneros ; Vivian et al ), it is likely that planted and remnant S. tabernaemontani stands would increase in size and extent if lake flows were more variable. A study by Catford et al () supports this fact, suggesting that hydrological regulation in the Murray River system limits the establishment of native plants adapted to variable flows while benefiting more invasive species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have suggested that environmental factors likely to influence reed bed expansion include seasonal fluctuations in water levels and nutrient influxes from the lake bottom and surrounding river systems (Liira et al ; Catford et al ). However, based on the response of other wetland plants and other Schoenoplectus species to seasonal water fluctuations and nutrient increases (Escutia‐Lara & Lindig‐Cisneros ; Vivian et al ), it is likely that planted and remnant S. tabernaemontani stands would increase in size and extent if lake flows were more variable. A study by Catford et al () supports this fact, suggesting that hydrological regulation in the Murray River system limits the establishment of native plants adapted to variable flows while benefiting more invasive species.…”
Section: Discussionmentioning
confidence: 99%
“…Although S. tabernaemontani appears to be relatively resilient to drought conditions, having survived the Millennium Drought and subsequent low water levels by resprouting from rhizomes after normal water levels returned to Lake Alexandrina and Lake Albert (Nicol et al ), a variety of factors may influence the persistence of this species. These include nutrient increases (Escutia‐Lara & Lindig‐Cisneros ), droughts and subsequent wetland drying (Catford et al ) and access to the shoreline by livestock and livestock grazing (Vanderbosch & Galatowitsch ). Greater research into how factors such as climate variability, water levels, soil nutrients, and lake substrates influence the establishment of sedge species may increase our ability to more effectively restore important wetland systems.…”
Section: Discussionmentioning
confidence: 99%
“… Dilute it in 50 mL of distilled water and observe the turn.  3 to 4 drops of 5% K2CrO4 were added (Escutia, 2012).  Adjust the pH to a range of 6.3 -10.5, that is, if the sample is less than 6.3, make it alkaline with sodium carbonate (NaHCO3), but if it is greater than 10.5, add acetic acid (CH3COOH).…”
Section: Procedures To Calculate the Total Hardness Of Well Watermentioning
confidence: 99%
“…habitat is being substituted by that of L. racemosa, whose habitat is in turn substituted by Conocarpus erectus, owing to reduction in depth of the lake basin, an increased inflow of freshwater, and a decrease in salinity. This horizontal dynamics is accompanied by an increase in the area occupied by Phragmites australis and Typha domingensis 22,23 , species whose optimal development occurs in sites with shallow standing water and low salinity, in contrast to the requirements for mangroves. Typical mangrove species are therefore being replaced by others from outside this type of community.…”
mentioning
confidence: 99%